Does a parental history of cancer moderate the associations between impaired health status in parents and psychosocial problems in teenagers: a HUNT study. (10th April 2014) - Jeppesen, Elisabeth; Bjelland, Ingvar; Fosså, Sophie D.; Loge, Jon H.; Sørebø, Øystein; Dahl, Alv A.
Abstract Severe disease in a parent is associated with increased psychosocial problems in their children. However, moderating factors of such associations are less studied. In this cross‐sectional population‐based controlled study we examined the moderating effects of a history of parental cancer on the association between impaired health status in parents and psychosocial problems among their teenagers. Among families with both parents responding to the adult Health Survey of Nord‐Trøndelag County of Norway (the HUNT‐2 study) 71 couples were identified with primary invasive cancer in one parent. Their 81 teenage children took part in the Young‐HUNT study. These families were compared to 322 cancer‐free families with 328 teenagers. Based on self‐report data the relations between three variables of parental impaired health and six psychosocial problems in teenagers were analyzed family wise by structural equation modeling. Significant associations between parental and teenagers' variables were observed in eight of 18 models. A history of parental cancer was a significant moderator which decreased four of eight significant associations. Such a history significantly weakened the associations between parental poor self‐rated health and teenagers' anxiety/depression and school problems. A similar association of a history of parental cancer was found between psychological distress in parents and teenagers' feelings of loneliness and poor self‐rated health. This study confirmed strong associations between impaired parental health and psychosocial problems in their teenagers. A history of parental cancer weakened several of the significant associations between parental impaired health variables and psychosocial problems in their teenagers.